2022
DOI: 10.4239/wjd.v13.i12.1066
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived exosomes: The dawn of diabetic wound healing

Abstract: Chronic wound healing has long been an unmet medical need in the field of wound repair, with diabetes being one of the major etiologies. Diabetic chronic wounds (DCWs), especially diabetic foot ulcers, are one of the most threatening chronic complications of diabetes. Although the treatment strategies, drugs, and dressings for DCWs have made great progress, they remain ineffective in some patients with refractory wounds. Stem cell-based therapies have achieved specific efficacy in various fields, with mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 163 publications
0
15
0
Order By: Relevance
“…This study hypothesised that injection of the tissue-permeable 35 kDa hyaluronan fragment HA35 into healthy skin immediately surrounding chronic wounds has therapeutic effects on alleviating chronic wound-related pain and enhancing chronic wound healing. 34,35 In this study, 20 patients with chronic wounds accompanied by pain were treated by injecting freshly manufactured tissue-permeable HA fragment HA35 into the tissue under healthy skin immediately surrounding the chronic wounds. The results indicated that the injection of HA35 relieved the pain associated with chronic wounds within 24 hours (Figure 2), suggesting HA35 can reduce the inflammatory pain caused by chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study hypothesised that injection of the tissue-permeable 35 kDa hyaluronan fragment HA35 into healthy skin immediately surrounding chronic wounds has therapeutic effects on alleviating chronic wound-related pain and enhancing chronic wound healing. 34,35 In this study, 20 patients with chronic wounds accompanied by pain were treated by injecting freshly manufactured tissue-permeable HA fragment HA35 into the tissue under healthy skin immediately surrounding the chronic wounds. The results indicated that the injection of HA35 relieved the pain associated with chronic wounds within 24 hours (Figure 2), suggesting HA35 can reduce the inflammatory pain caused by chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Caires et al in Nature Communications reported that HMWHA reduced TRPV1 channel opening, 33 reducing peripheral nociceptor activity and pain, supporting the pain‐relieving effect of HA35. This study hypothesised that injection of the tissue‐permeable 35 kDa hyaluronan fragment HA35 into healthy skin immediately surrounding chronic wounds has therapeutic effects on alleviating chronic wound‐related pain and enhancing chronic wound healing 34,35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria were applied to filter out the studies that did not meet the research goals, such as: (1) in vitro studies, (2) review articles, (3) non-English-language publication, (4) studies unrelated to wound healing, (5) no full access to the publication, and ( 6) studies not involving exosomes.…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of ADSCs for the treatment of obesity-related disorders could not be limited to chronic wounds. In fact, ADSC-derived exosomes have been shown to inhibit both adipogenic differentiation and lipogenesis in ADSCs through activation of the Hedgehog (Hh) pathway [ 165 , 166 ]. Despite the promising results achieved with MSCs in the treatment of diabetes and its associated comorbidities, clinical data on the efficacy of autologous ADSCs are still lacking [ 167 , 168 ].…”
Section: Mscs and Wound Healingmentioning
confidence: 99%